(untitled) (Journal of Hama University, 2021)
Endodontic treatment has a unique and complicated nature that makes errors and complications very possible to take place during treatment steps. The separation of endodontic instrument is one of the most serious problems to general practitioners and specialists during treatment; because of the difficulty to deal with it; due to several variables. The aim of this research is to determine the success rate of removing separated files in root canals using ultrasonic technique according to 2 variables: position of the separated instrument in the canal, and curvature of the canal, and its effect on the mechanical resistance of the root. The sample consists of 80 single-canal recently extracted human teeth (40 straight, 40 curved). The findings exhibited a success rate of 92.5% in removing separated files. Success rate in straight canals was significantly higher than that in curved ones, also in middle third compared with apical one. In this context, all samples exhibited a decrease in mechanical resistance after separated instrument retrieval attempt with no significant difference between groups. We conclude that ultrasonic is an effective technique to remove separated instruments from root canals especially in straight ones, yet it affects the root fracture resistance regardless of the root curvature or position of the instrument. The data obtained was statistically analyzed using Chi-Square of independent means test, Mann-Whitney U test and independent two-sample t test. (P <0.05)